2016
DOI: 10.4049/jimmunol.1502006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30c Modulates Type I IFN Responses To Facilitate Porcine Reproductive and Respiratory Syndrome Virus Infection by Targeting JAK1

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an economically important pathogen and has evolved several mechanisms to evade IFN-I responses. We report that a host microRNA, miR-30c, was upregulated by PRRSV via activating NF-κB and facilitated its ability to infect subject animals. Subsequently, we demonstrated that miR-30c was a potent negative regulator of IFN-I signaling by targeting JAK1, resulting in the enhancement of PRRSV infection. In addition, we found that JAK1 expression was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 48 publications
2
45
2
Order By: Relevance
“…FOS (FBJ murine osteosarcoma viral oncogene homolog), as a cellular immediate-early gene was markedly induced before expressions of the Epstein-Barr Virus (EBV) transactivator genes were activated [35], which was similar in the process of IBDV infection. Likewise, host immune-related genes, such as VCAM1, NFKB1 and TLR2/3, were also elevated at the early stage in the infection group, which were consistent with many previous reports [3638]. …”
Section: Discussionsupporting
confidence: 92%
“…FOS (FBJ murine osteosarcoma viral oncogene homolog), as a cellular immediate-early gene was markedly induced before expressions of the Epstein-Barr Virus (EBV) transactivator genes were activated [35], which was similar in the process of IBDV infection. Likewise, host immune-related genes, such as VCAM1, NFKB1 and TLR2/3, were also elevated at the early stage in the infection group, which were consistent with many previous reports [3638]. …”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of NF-B activation by pyrrolidine dithiocarbamate leads to a significant decrease in the levels of heparanase (20), indicating that NF-B might be an important regulator of heparanase. A number of reports have also demonstrated that PRRSV infection can activate the NF-B signaling pathway by IB␣ degradation and nuclear translocation of p65, a key subunit of NF-B (21,22). We therefore investigated the possible connection between NF-B and heparanase after PRRSV infection.…”
Section: Resultsmentioning
confidence: 96%
“…TGEV infection downregulates miR-30a-5p expression. The host miR-30 family (five members, consisting of miR30a to miR30e) plays important roles in cancers and viral infections (30,34,36,37). We recently reported that miR-30a-5p, a member of the miR-30 family, is downregulated and that is expression is inversely correlated with the levels of ER stress in renal cancer, indicating that ER stress might inhibit miR-30a-5p expression (34).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a mutant vector was constructed to eliminate possible recognition by replacing five seed nucleotides (in which the underlined nucleotides in the sequence UGUUUAC were changed, resulting in the sequence UAGGGUC) as previously described (Fig. 5A) (30). Compared with the NC mimic treatment, overexpression of miR-30a-5p in ST cells decreased the activity of the luciferase reporter containing the SOCS1 or SOCS3 wild-type target sequence but not that of the luciferase reporter containing the mutant target site of SOCS1 or SOCS3.…”
Section: Resultsmentioning
confidence: 99%